Analisis Perbedaan Kadar Glukosa Darah Sewaktu Dengan Antikoagulan Edta Dan Naf Pada Mahasiswa Tingkat Akhir - Inka Fitra Rahmadani; Fitria Milanda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Random blood glucose (RBG) testing is one of the clinical chemistry examinations whose results may be affected by delayed analysis due to the glycolysis process. The use of an appropriate anticoagulant is essential to maintain glucose stability. Sodium fluoride (NaF) is known to inhibit glycolysis, whereas Ethylenediaminetetraacetic Acid (EDTA) is more commonly used for hematological examinations but is still occasionally used for glucose testing. The different characteristics of these anticoagulants may influence the accuracy of glucose measurements; therefore, further evaluation is necessary. This study aimed to analyze the differences in random blood glucose levels measured using EDTA plasma and sodium fluoride (NaF) plasma in final-year students. This experimental study employed a comparative design involving two types of anticoagulants using blood samples collected from 20 respondents. Venous blood samples were collected using a vacutainer system, with 3 mL drawn into an EDTA tube and 2 mL into a NaF tube. Random blood glucose levels were measured using the enzymatic hexokinase method. The results showed that the mean random blood glucose level was 86.05 mg/dL in EDTA plasma and 89.80 mg/dL in NaF plasma, with a mean difference of 3.75 mg/dL. The paired t-test demonstrated a statistically significant difference between the two sample types. NaF plasma produced higher glucose levels than EDTA plasma because it effectively inhibited glycolysis, thereby maintaining glucose stability throughout the analytical process.